QUR’ANIC SELF-DIRECTED LEARNING - Rosidin, Rosidin (STAI Ma'had Aly Al-Hikam Malang, 2015)
Contemporary education has new paradigms, lifelong education and learning how to learn. To realize the two both paradigms, it is necessary to educate students in order to become self-directed learners. A self-directed learner has high capacity of Self-Directed Learning that contains self-teaching and personal autonomy. One side, self-teaching ability reduces his dependences to educators; other side personal autonomy ability increases his self-directed to learn. This article proposes alternative ideas of Self-Directed Learning, particularly on education methods to develop and capacity training of Self-Directed Learning in the perspective of education exegesis (tafsîr tarbawî) with al- Qur’an as the primer resource and of course evolved secondary resources, books of exegesis (kutub tafsîr) with some additional relevant literatures.